2022
DOI: 10.3390/ijerph19052775
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving of Older Persons during the COVID-19 Pandemic in the Russian Arctic Province: Challenges and Practice

Abstract: Older people and their families were particularly affected during the COVID-19 pandemic in 2020, but not much is known about the context of the Arctic regions of Russia. In this study, we identified the changes in family care before and during the pandemic using a questionnaire for the informal caregivers of older people. We investigated how and to what extent the pandemic has affected the relationships between caregiver and older person, and how the mental and physical health of older people and caregivers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Role of Risk Perception Golubeva et al (2022), in their study in Russia, found that the most significant concerns reported by the family caregivers of the elderly were the health of the elderly, reduced access to healthcare services, and a fear of infecting the household with COVID-19 [27]. Similarly, the current study documented that higher risk perception about the elderly patient's health status, infectivity, and scarcity of health resources lead the home-based family caregivers to decide against home isolation, independent of the clinical condition of the elderly [28].…”
Section: Findings In the Light Of Relevant Literaturementioning
confidence: 99%
“…Role of Risk Perception Golubeva et al (2022), in their study in Russia, found that the most significant concerns reported by the family caregivers of the elderly were the health of the elderly, reduced access to healthcare services, and a fear of infecting the household with COVID-19 [27]. Similarly, the current study documented that higher risk perception about the elderly patient's health status, infectivity, and scarcity of health resources lead the home-based family caregivers to decide against home isolation, independent of the clinical condition of the elderly [28].…”
Section: Findings In the Light Of Relevant Literaturementioning
confidence: 99%
“…Previous studies have demonstrated the distinct challenges the Arctic faces in relation to the COVID-19 pandemic and potentially similar public health or infectious disease emergencies. Markova et al 37 , Lemieux et al 38 , Simonen et al 39 , Cook & Johannsdottir [ 40 ], Men & Tarasuk 41 , and Golubeva et al 42 ,all have pointed out that the COVID-19 pandemic has exacerbated the existing socioeconomic vulnerability, food insecurity and health outcomes of the Arctic residents. The pandemic has pushed the people of Sakha (Northeastern Siberia, Russia) into poverty as people have lost their jobs and lacked stable earnings (overdue wage arrears) [ 37 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cook & Johannsdottir [ 40 ] developed a multiscale framework to assess the impact of COVID-19 on Iceland and Greenland across seven categories [economic, environmental, social-cultural, business, ethical, health, science/education) and found that the pandemic has presented risks in both countries across all categories. Golubeva et al 42 ,uncovered that self-isolation measures led to deterioration in the mental and physical health of older people as well as of caregivers living in the Russian Arctic.…”
Section: Introductionmentioning
confidence: 99%